Chronique juridique - Létourneau, Alain (Assurances)

(untitled) (HEC Montréal, 1982)
In a recent ruling, the Honourable Jean Beauregard presented a study on the access to class actions and proper compensation in matters of insurance. Our contributing legal writer, Me Alain Létourneau, summarizes hereinbelow the major elements of this study for our readers.